Board Governance Mechanisms and Sustainability Disclosure: A Moderating Role of Intellectual Capital - Baba, Bello Usman; Abdul Manaf, Kamarul Bahrain
The purpose of this paper is to investigate the extent and determinants of sustainability disclosure practice in Nigeria.The second objective is to examine if the effectiveness of intellectual capital moderates the relationship between board governance mechanisms and sustainability disclosure.In the course of carrying out this research, content analysis was conducted to extract sustainability disclosure information from annual reports of 80 companies listed on Nigerian Stock Exchange. The study spanned from 2010-2015. Board size, board independence, board diversity and board meetings were considered as determinants of sustainability disclosure.The sustainability disclosure index and board governance measures were computed for estimation of the regression analysis.The percentages were used to describe the nature and extent of sustainability disclosure among the sampled companies. A multiple regression analysis was used to test the relationships specified in the study.The result of the descriptive analysis evidence a low-level disclosure of sustainability information in annual reports of companies.From the regression analysis, board size, board independence and board diversity were found to enhance the disclosure of sustainability information.However, board meeting was found to be insignificantly related to sustainability disclosure.The results also reveal that intellectual capital has a significant positive effect on the relationship between board size, board independence, board diversity and sustainability disclosure. However, intellectual capital does not seem to moderate the relationship between board meetings and sustainability disclosure.The findings from this study have both theoretical and practical implications.